PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR SISWA SMP - Fransiska Evelina Kune; Finsensius Yesekiel Naja; Ariswan Usman Aje (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to determine (1) student learning activities in the learning process after applying the STAD type cooperative learning model for triangle material in class VII students of SMP Negeri 3 Ende; (2) the improvement of students' mathematics learning outcomes through a cooperative approach to class VII STAD type of SMP Negeri 3 Ende. The type of research used is Classroom Action Research. The subjects in this study were 20 class VII A students at SMP Negeri 3 Ende. Data collection techniques carried out were tests, observations, and documentation. The data analysis technique used is individual learning completeness, classical completeness and the percentage of learning outcomes. The results showed that the overall cycle I and cycle II experienced an increase. The percentage increase in the implementation of teacher activities was 15.6% in the very good category, the percentage of student involvement and activity was 20% in the very good category and the percentage increase in classical completeness was 25% in the very good category. From the results of these observations and analysis, it can be concluded that the Cooperative Learning Model type Student Teams Achievement Division (STAD) should increase activity and learning outcomes for triangle material in class VII students of SMP Negeri 3 Ende.